A scoping review of the risk factors and strategies followed for the prevention of COVID-19 and other infectious diseases during sports mass gatherings: Recommendations for future FIFA World Cups - Nour Waleed Zuhair Alhussaini; Usra Abushara Mohamed Elshaikh; Noor Ahmed Hamad; Maisa Ayman Nazzal; Manal Abuzayed; Ghadir Fakhri Al-Jayyousi (Frontiers Media S.A., 2023)
ObjectiveSports mass gatherings of people pose particular concerns and place an additional burden on the host countries and the countries of origin of the travelers. It is imperative to identify how countries dealt with various communicable diseases in the context of previous world cups and identify possible advice for protection from outbreaks.MethodsA scoping review was employed in this study and a PRISMA extension for scoping reviews was employed to guide the reporting of this study. A systematic search was performed using PubMed, Embase, Web of Science, SCOPUS, SportDiscus, and Google scholar. The search strategy included two main strings viz "communicable disease" AND "sport" AND "setting" as keywords for each string. A total of 34 studies were included in this review.ResultsInformation on risk factors for infectious diseases during FIFA, and recommendations for disease prevention in various stages of the event: pre-event, during, and post-event were charted. These strategies can be achieved with the empowerment of the public by enhancing their social responsibility and the coordination between the healthcare system, the ministry of public health, and other stakeholders.ConclusionThe findings will support planning for protection strategies to prevent any outbreak while having the FIFA World Cup or any other sports gatherings. A model was constructed to present the findings and recommendations from this review.